PELATIHAN PENGENALAN PEMROGRAMAN MOBILE BERBASIS ANDROID PADA SISWA SMK NEGERI 4 BANJARMASIN - Mantala, Ronny; Sari Hepy Maharani; Tarman Effendi (Jurnal IMPACT: Implementation and Action, 2023)
The Mobile Programming Introduction Training was conducted to enhance the knowledge and skills of students at SMK Negeri 4 Banjarmasin, particularly those in the Software Engineering Department, in mobile application development. This training aimed to provide foundational knowledge in Android programming using Java, a dominant platform in the mobile app development world. The event was attended by 20 second-year students and involved lectures, hands-on practice, and interactive discussions. The results of the training indicate that participants successfully understood and applied the concepts taught, as evidenced by their ability to create simple Android applications. Despite challenges related to time constraints, the training positively impacted the students' readiness for the increasingly digital job market. Thus, the training is expected to contribute to the development of students' competencies and open career opportunities in the information technology field.